2015
DOI: 10.3389/fnhum.2015.00619
|View full text |Cite
|
Sign up to set email alerts
|

The Eye is Listening: Music-Induced Arousal and Individual Differences Predict Pupillary Responses

Abstract: Pupillary responses are a well-known indicator of emotional arousal but have not yet been systematically investigated in response to music. Here, we measured pupillary dilations evoked by short musical excerpts normalized for intensity and selected for their stylistic uniformity. Thirty participants (15 females) provided subjective ratings of music-induced felt arousal, tension, pleasantness, and familiarity for 80 classical music excerpts. The pupillary responses evoked by these excerpts were measured in anot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 87 publications
8
53
3
1
Order By: Relevance
“…Thus, our study provides new knowledge by adopting a two-dimensional framework in concert with diverse psychophysiological measures (cf. Gingras, Marin, Puig-Waldmüller, & Fitch, 2015) to better examine multiple components of music-evoked emotional experiences.…”
Section: Defining and Conceptualizing Musical Emotionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our study provides new knowledge by adopting a two-dimensional framework in concert with diverse psychophysiological measures (cf. Gingras, Marin, Puig-Waldmüller, & Fitch, 2015) to better examine multiple components of music-evoked emotional experiences.…”
Section: Defining and Conceptualizing Musical Emotionsmentioning
confidence: 99%
“…Finally, by collecting subjective ratings and physiological measures from separate groups of listeners, we were able to mitigate the influence of subjective rating tasks on physiological responses. This issue has been discussed as a shortcoming of previous psychophysiological studies in music and emotion, and some authors have suggested that concurrently performing a task might alter the physiological results Psychophysiological Indices of Musical Emotions 12 (Gingras, et al, 2015;White & Rickard, 2015) in addition to behavioral demand characteristics.…”
Section: The Present Studymentioning
confidence: 99%
“…Hess and colleagues reported that human pupils dilate in response to appealing images and statements (Hess and Polt, 1960;Hess, 1965;Hess et al, 1965). Since then, pupillometric investigations have been used in numerous studies to investigate emotional responses to visual (Bradley et al, 2008) or auditory presentation (Partala and Surakka, 2003;Gingras et al, 2015). Dilation of the pupils can also indicate cognitive load (Steinhauer et al, 2004;Eckstein et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Pupillary dilatation results also from pleasant sounds and melodies. Known music tracks enhance pupillary diameters but not unknown and less salient melodies [155][156][157][158][159][160][161][162] . Finally, measures of pupillary diameter may also reveal active mental efforts associated with coping strategies such as reappraisal or suppression of negative emotions 163 164-171 .…”
Section: Pupillary Dilatation: Cognitionmentioning
confidence: 99%